2020
DOI: 10.3923/ajps.2020.191.199
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Desert Dam Reservoir in Arid Habitat

Abstract: Background and Objective: Although desert dams create storage reservoirs that recharge ground water, irrigate desert agriculture and protect against flash floods, there is controversy about their effects on ecosystem. Work in this study was carried out to provide first environmental impact assessment of Wadi Jazan desert reservoir by studying its effects on soil and floristic composition. Materials and Methods: Soil analysis included studies of soil types and characteristics. Vegetation analysis included study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
6
1
Order By: Relevance
“…The dominance of annual herbs (39.74%) followed by perennial herbs (18.54%) was might be due to the availability of more moisture created by dams in those areas and secondly due to their short life cycle pattern that helps them to resist the instability of the ecosystem ( Alatar et al, 2012 , Gomaa, 2012 , Mahmoud et al, 2018 ). Our results are comparable with the study of Sayed et al, (2020) on the impact of Wadi Jizan desert reservoir which reported that the area around the reservoir harbored several plant species with different life forms and a prevalence of annuals and perennials herbs. Chorological analysis of the surveyed plants revealed the dominance of monoregional elements (57.623%), over the biregionals (27.81%) and pluriregionals, and the presence of the biregional and pluriregonal due to Saudi consider as a meeting point of Africa, South Europe and Asia ( Alatar et al, 2012 , Al-Sherif et al, 2013 , Osman et al, 2014 , Abdel Khalik et al, 2017 , Mahmoud et al, 2018 , Al-Yasi et al, 2019 , Al-Shehri et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The dominance of annual herbs (39.74%) followed by perennial herbs (18.54%) was might be due to the availability of more moisture created by dams in those areas and secondly due to their short life cycle pattern that helps them to resist the instability of the ecosystem ( Alatar et al, 2012 , Gomaa, 2012 , Mahmoud et al, 2018 ). Our results are comparable with the study of Sayed et al, (2020) on the impact of Wadi Jizan desert reservoir which reported that the area around the reservoir harbored several plant species with different life forms and a prevalence of annuals and perennials herbs. Chorological analysis of the surveyed plants revealed the dominance of monoregional elements (57.623%), over the biregionals (27.81%) and pluriregionals, and the presence of the biregional and pluriregonal due to Saudi consider as a meeting point of Africa, South Europe and Asia ( Alatar et al, 2012 , Al-Sherif et al, 2013 , Osman et al, 2014 , Abdel Khalik et al, 2017 , Mahmoud et al, 2018 , Al-Yasi et al, 2019 , Al-Shehri et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Dam construction is one of the main strategies for storing and protecting runoff water for consumption and agricultural needs. Despite these socioeconomic roles, desert reservoirs fell into controversy because of their complex impact on desert ecosystems such as their influence over climate, ability to modify sedimentation patterns, facilitate the establishment of many plant species and last but not least their impact on regional floristic diversity ( Sayed et al, 2020 , Šulyová et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, [7] also revealed that the genetic diversity and genetic relationships of 39 lime genotypes had been successfully evaluated through morphological analyses. In addition to morphological characterization, [8] reported that the differences among acid citrus accessions were obtained by observing leaf lamina and fruit shape. This study was supported by [9] who reported that morphological traits such as leaves and fruit could evaluate the difference in Citrus Grandi's genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…ISSR marker mostly has been used in citrus species identification, because it could separate citrus species as well as varieties into proper clusters [8]. However, [12] revealed that the genetic similarities of the lemon group derived from morphological (75%) and molecular analyses (73%) were not different.…”
Section: Introductionmentioning
confidence: 99%